Surgical Management Of Nonhealing Extra-Oralcutaneous Pus Draining Sinus Tract Of Odontogenic Origin. A Case Report (International Journal of Food and Nutritional Sciences, 2022)
Inflammation in a circumscribed area may lead to development of a path to the epetlial surface,this in turn leads to the development of cuataneous sinus. For evaluation, diagnosis, and treatment of the same, patient visits physician first resulting in no consideration for dental etiology most of the times. Sometimes the ignorance and misdiagnosis can lead to persistence of infection resulting in recurring sinus. Successful management of the odontogenic cutaneous sinus requires proper diagnosis. A male patient, Presented with skin lesions of odontogenic etiology with discharging sinus, and unresponsive to antibiotics. The patient was treated by surgical excision of Cutaneous Sinus tract along with Extraction of offending tooth.